Дослідження напружено-деформованого стану дна кузова напівпричіпа вантажного автомобіля в залежності від розміщення перемичок - Гевко, Ів. Б.; Пиндус, Ю. І.; Левкович, М. Г.; Тесля, В. О.; Гупка, А. Б.; Сіправська, М. Д.; Hevko, I.; Pyndus, Yu.; Levkovich, M.; Teslia, V.; Gupka, А.; Sipravska, M. (ЦНТУ, 2023)
За допомогою методу напруження-деформації було проведено комплексне дослідження кузовів вантажних напівпричепів, що призвело до розробки інноваційних інженерних рішень, спрямованих на підвищення їх техніко-економічних показників. Це було досягнуто шляхом аналізу впливу різних факторів на особливості будови та конструкції. Результати дослідження були отримані на основі напружено-деформованого стану (НДС) з використанням передових методів інженерного аналізу, зокрема із застосуванням спеціалізованого програмного комплексу SolidWorks на CAD-моделі, що представляє кузов напівпричепа вантажівки. The purpose of this article is to study the influence of the geometric parameters of the elements of the bottom of the body of a truck semi-trailer on its stress-strain state. To solve this problem, a combination of analytical, numerical and experimental methods is used to investigate the stress-strain state of the structure in car bodies. With help of the stress-strain method, a comprehensive study of the bodies of cargo semi-trailers was carried out, which led to the development of innovative engineering solutions aimed at increasing their technical and economic indicators. This was achieved by analyzing the influence of various factors on the structure and design features. The research results were obtained on the basis of the stress-strain state (SST) using advanced methods of engineering analysis, in particular, using the specialized SolidWorks software complex on a CAD model representing the body of a semi-trailer truck. The results obtained after conducting these studies serve as the basis for making engineering decisions aimed at improving the design of the truck body.
Study of the Stress-Deformation State of the Bottom of the Semi-Trailer Truck Body Depending on the Placement of the Jumpers
Keywords: вантажний автомобіль; напівпричіп; конструкція; напружено-деформований стан; геометричні параметри; truck; semi-trailer; construction; stress-strain state; geometric parameters